2023
DOI: 10.1097/nmc.0000000000000930
|View full text |Cite
|
Sign up to set email alerts
|

The Oral Microbiome Throughout Pregnancy

Abstract: Introduction:Oral health is associated with systemic health, including adverse pregnancy outcomes. Understanding the oral microbiome during pregnancy may lead to targeted interventions for prevention of adverse outcomes. The purpose of this review is to examine the literature on the oral microbiome throughout pregnancy.Methods:We conducted a literature search with four electronic databases for original research conducted between 2012 and 2022 that examined the oral microbiome longitudinally using 16s rRNA sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
(145 reference statements)
0
2
0
Order By: Relevance
“…Many studies found an association between the nearest and farthest anatomical sites of a sampling microbiome and found strong interconnections [ 3 , 19 , 31 , 32 , 33 ]. Similarly, a recent scoping review [ 50 ] provides valuable insights into the oral microbiome of preterm infants, complementing our focus on the airway. The review emphasizes the interconnectedness of oral and airway microbiomes, hinting at potential seeding reservoirs for respiratory microbes.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies found an association between the nearest and farthest anatomical sites of a sampling microbiome and found strong interconnections [ 3 , 19 , 31 , 32 , 33 ]. Similarly, a recent scoping review [ 50 ] provides valuable insights into the oral microbiome of preterm infants, complementing our focus on the airway. The review emphasizes the interconnectedness of oral and airway microbiomes, hinting at potential seeding reservoirs for respiratory microbes.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited research on the composition of the oral microbiome throughout pregnancy. There may be alterations in the oral microbiome during pregnancy such as increased relative abundance of pathogenic bacteria (Koerner et al, 2023). The distribution and clustering of oral microbiome for gingivitis among women at 3 months of pregnancy have not been explored and this especially in the interdental spaces.…”
Section: Introductionmentioning
confidence: 99%